2018
DOI: 10.5902/1980509831635
|View full text |Cite
|
Sign up to set email alerts
|

PRODUTIVIDADE DE MICROCEPAS DE GRÁPIA (<i>Apuleia leiocarpa</i>) MANTIDAS<i> IN VITRO</i>

Abstract: RESUMOO objetivo deste trabalho foi avaliar a produtividade de microcepas de grápia (Apuleia leiocarpa) mantidas em diferentes condições de cultivo in vitro, visando maximizar a taxa de multiplicação. Microcepas oriundas da poda drástica de plantas assépticas foram cultivadas em meio de cultura WPM acrescido de 0; 2,2; 4,4; 6,6 e 8,8 µM de 6-benzilaminopurina (BAP) e subcultivadas em meio de cultura WPM sem citocinina. Microcepas de grápia também foram cultivadas em meio de cultura WPM, MS ou ½ MS, acrescido o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…In this context, the use of activated charcoal (Me1) or PVP30 (Me2) in the culture medium or exposure to light for Ontogenetic age and inoculation methods for the in vitro establishment of Eucalyptus pilularis Smith Nativa, Sinop, v. 10, n. 1, p. 40-46, 2022. 44 30 days (Me3) reduced the oxidation of E. pilularis tissues. The adsorption of phenolic compounds and toxic substances by activated charcoal during the in vitro culture of woody species has the advantage of reducing tissue oxidation, which can improve and regulate the in vitro growth under certain conditions (FAGUNDES et al, 2017;LENCINA et al, 2018), corroborating the results of the present study. However, few studies have reported its effects according to ontogenetic age.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this context, the use of activated charcoal (Me1) or PVP30 (Me2) in the culture medium or exposure to light for Ontogenetic age and inoculation methods for the in vitro establishment of Eucalyptus pilularis Smith Nativa, Sinop, v. 10, n. 1, p. 40-46, 2022. 44 30 days (Me3) reduced the oxidation of E. pilularis tissues. The adsorption of phenolic compounds and toxic substances by activated charcoal during the in vitro culture of woody species has the advantage of reducing tissue oxidation, which can improve and regulate the in vitro growth under certain conditions (FAGUNDES et al, 2017;LENCINA et al, 2018), corroborating the results of the present study. However, few studies have reported its effects according to ontogenetic age.…”
Section: Discussionsupporting
confidence: 89%
“…The use of antioxidants in the culture medium, such as activated charcoal and polyvinylpyrrolidone (PVP), and different incubation conditions regarding lighting are ways to reduce tissue oxidation and contamination by microorganisms, making a successful in vitro establishment more likely (FAGUNDES et al, 2017;LENCINA et al;2018;GOLLE et al, 2020). However, there is a need to define the ideal asepsis conditions for each species according to the origin of the tissues.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important step for micropropagation of plants, and is essential for the rescue of selected plants, or those with a lack of seeds for in vitro establishment. Once established, explants can be multiplied following the methodology described by Lencina et al (2016;2017a), rooted in vitro in WPM culture medium supplemented with 1.0 mg L -1 of NAA, and acclimated according to Lencina et al (2017b). Therefore, the results of this study, combined with those of Lencina et al (2014;2016;2017a;2017b), provide a complete micropropagation methodology and, as a result, an in vitro conservation strategy for grápia, a native species that is of ecological interest and an important timber species that is threatened with extinction.…”
Section: Resultsmentioning
confidence: 99%
“…As such, studies that address the identification of production technologies for grápia seedlings are relevant, and micropropagation may be an option for propagation of this species. Studies related to the vegetative propagation of grápia have been carried out in recent years, and such studies have led to the establishment of aseptic plants to supply explants (LENCINA et al, 2014), in vitro multiplication (LENCINA et al, 2016;2017a), in vitro and ex vitro rooting, and plant acclimatization (LENCINA et al, 2017b). However, no previous studies have addressed the introduction of propagules in vitro, and there is little available data related to adventitious rooting in grápia.…”
Section: Introductionmentioning
confidence: 99%
“…In Hancornia speciosa Gomes stem explants, SOARES et al (2011) reported a greater number of shoots at the end of the preculture due to the presence of BAP in the culture medium, and the values remained constant in three subcultures. According to LENCINA et al (2018), supplementation of the nutrient medium with BAP (2 mg L -1 ) and subsequent subculture in culture medium without this cytokinin favors shoot induction and growth in Apuleia leiocarpa microstumps.…”
Section: In Vitro Multiplicationmentioning
confidence: 99%